1995
DOI: 10.1074/jbc.270.24.14477
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of TAFI, a Thrombin-activable Fibrinolysis Inhibitor

Abstract: Previous studies demonstrated that tissue plasminogen activator-induced fibrinolysis in vitro is retarded in the presence of prothrombin (II) activation and that the anticoagulant-activated protein C appears profibrinolytic by preventing the formation of thrombin (IIa)-like activity during fibrinolysis. To disclose the molecular connection between the generation of IIa and the inhibition of fibrinolysis, a lysis assay that is sensitive to the antifibrinolytic effect of II activation was developed and was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
628
1
12

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 676 publications
(653 citation statements)
references
References 37 publications
9
628
1
12
Order By: Relevance
“…Under physiological conditions, liver cells are the main source of TAFI production, and during inflammation TAFI acts as an acute reactant protein as demonstrated in mice [18,26]. We have previously demonstrated that, in addition to hepatic cells, adipocytes, endothelial, and epithelial cells may also produce and secrete TAFI in vitro [21,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under physiological conditions, liver cells are the main source of TAFI production, and during inflammation TAFI acts as an acute reactant protein as demonstrated in mice [18,26]. We have previously demonstrated that, in addition to hepatic cells, adipocytes, endothelial, and epithelial cells may also produce and secrete TAFI in vitro [21,27].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new potent inhibitor of fibrinolysis, the thrombin-activatable fibrinolysis inhibitor (TAFI) or carboxypeptidase U, has been isolated and characterized from human plasma [18]. TAFI is a glycoprotein synthesized by the liver that can be activated by thrombin-catalyzed proteolysis to a carboxypeptidase B-like enzyme that inhibits fibrinolysis.…”
Section: Introductionmentioning
confidence: 99%
“…An important regulator of the interaction between fibrin, plasminogen and t-PA is exerted by carboxypeptidase U (CPU), also known as active Thrombin Activatable Fibrinolysis Inhibitor (TAFIa) [36,37]. The proposed mechanism of action of CPU in clotting plasma is that it removes C-terminal lysine residues from partly degraded fibrin, which results in lower plasminogen binding, and thereby lower plasmin generation and a retarded lysis rate.…”
Section: Hepatic Clearencementioning
confidence: 99%
“…The Gusto IIB trial [164] showed that hirudin and heparin in combination with rt-PA produced similar effects on the combined endpoints death and myocardial infarction in patients with acute myocardial infarction. It had been suggested that thrombin trapped in, or bound to, the fibrin in a thrombus may play an important role in resistance to thrombolysis and subsequent reocclusion [37,141]. It was therefore hypothesised that a small, potent thrombin inhibitor (MW 429) could be more effective in inhibiting fibrin-bound thrombin than the heparin: antithrombin complex (MW ≈75000) and the polypeptide hirudin (MW ≈7000).…”
Section: Thrombolysis and Thrombin Inhibition -Paper IImentioning
confidence: 99%
“…Thrombin plays a critical role in coagulation and the fibrinolytic system ( (8)(9)(10). These residues are important for binding and activating plasminogen.…”
Section: Hypothyroidism Is a Frequent Endocrine Disorder In The Genermentioning
confidence: 99%